Does Financial Sector Development facilitate in the ASEAN Economic Community’s Financial Integration? - S. Patiu, Liberty (International Journal of Engineering and Technology, 2018)
The development of the financial services industry is crucial to the harmonious financial integration in East Asia.  The ASEAN region is a host of member states with different levels of financial and economic developments.  This study determines the level of development in the financial services sector among the ASEAN5 member states from 2002 to 2013 and explores the opportunities where financial integration may be undertaken in the light of the establishment of the ASEAN Economic Community in 2015.  Member states exhibited high economic growth levels since the Asian Financial Crisis, which was spurred by the heightened competitiveness in the region brought about by the increase in inter- and intra-regional trade, investments and production network.  It was found that there is high intermediation in the financial system and majority of the ASEAN5 Member States still employ the bank-based financial system compared to non-banks and financial markets.  The region will slowly shifts from bank-based to market-based system, as changes in the financial architecture will become increasingly evident in the near future to enable smooth transition of the region into an economically integrated region.  Financial supervisors are faced with the challenges of providing sound financial environment, strong supervisory/regulatory framework and better institutional arrangements to stimulate further development of the financial services industry. Advanced economies will lead the region in increasing depth, in promoting financial soundness and in deepening collaboration among member states where reform priorities and financial convergence are crucial.